2010
DOI: 10.1016/j.ijid.2010.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocarditis in dengue hemorrhagic fever: a case report and review of cardiac complications in dengue-affected patients

Abstract: We report a case of dengue hemorrhagic fever (DHF) complicated by acute myocarditis and review the literature. A 65-year-old woman experienced DHF due to dengue virus serotype 3, complicated with acute myocarditis and acute pulmonary edema. Clinically this masqueraded as acute myocardial infarction, with an electrocardiographically depressed ST segment in precordial leads and elevated serum cardiac-specific troponin I level. Under supportive management, the patient recovered 3 days later. A total of 18 pertine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 24 publications
7
69
0
7
Order By: Relevance
“…Although, ST-segment and T-wave changes in the electrocardiogram (ECG) along with regional wall motion abnormality, mimicking acute MI, as a presentation, is very rare. 7,8 In the Medline search, like in our case, only two similar cases of dengue myocarditis mimicking acute MI have been reported so far. 7,8 The first one reported by Lee et al, 7 was a 25-year-old male, who presented with acute pulmonary edema and cardiogenic shock.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Although, ST-segment and T-wave changes in the electrocardiogram (ECG) along with regional wall motion abnormality, mimicking acute MI, as a presentation, is very rare. 7,8 In the Medline search, like in our case, only two similar cases of dengue myocarditis mimicking acute MI have been reported so far. 7,8 The first one reported by Lee et al, 7 was a 25-year-old male, who presented with acute pulmonary edema and cardiogenic shock.…”
Section: Discussionmentioning
confidence: 66%
“…He had ECG features suggestive of anterior wall MI, and died. Another case reported by Lee IK et al, 8 was a 65-year-old female who presented with DHF. She had significant ST-segment depression in the chest leads V3eV6, but survived.…”
Section: Discussionmentioning
confidence: 94%
“…There have been reports of acute myocarditis, as well as myopericarditis, pericarditis, asymptomatic myocardial dysfunction and cardiac rhythm disturbances, such as atrioventricular blocks, sinus node dysfunction, ventricular ectopic beats, atrial fibrillation, ST-segment and T-wave changes, tachycardia and bradycardia [3,[14][15][16][17][18][19]. Electrocardiogram abnormalities have been reported during the entire course of dengue.…”
Section: Casementioning
confidence: 99%
“…Abnormalities basically consist of sinus bradycardia, T inversion, depression of ST segment in precordial leads and avF, AV blocks, (Mobitz type I second degree has been mentioned) bundle branch blocks and rarely, atrial fibrillation 33, 34, 37, 38 . All were reported as supposedly transient 39 . Two cases of remaining atrial fibrillation after the resolution of disease have been reported, with reversion only achieved after antiarrhythmic treatment (Amiodarone) 39 .…”
Section: Resultsmentioning
confidence: 99%
“…All were reported as supposedly transient 39 . Two cases of remaining atrial fibrillation after the resolution of disease have been reported, with reversion only achieved after antiarrhythmic treatment (Amiodarone) 39 .…”
Section: Resultsmentioning
confidence: 99%